2nd International Conference on Nanomaterials Science and Mechanical Engineering: book of abstracts - Bdikin, Igor (2019)
2nd International Conference on Nanomaterials Science and Mechanical Engineering: book of abstracts - University of Aveiro, Portugal July 9-12, 2019.